Prolonged Thoracic Epidural Anesthesia in the Correction of Hypoxia in the Postoperative Period - P. A. Lyuboshevsky; A. V. Zabusov; I. L. Denisenko (Общая реаниматология)
Objective: to reduce the incidence of postoperative complications after high-risk abdominal surgery. Subjects and methods. The study enrolled 69 patients undergoing operations on the upper abdomen. The patients were randomized into 2 groups: 1) those who received total intravenous anesthesia with prolonged thoracic epidural anesthesia (a study group); 2) those who had total intravenous anesthesia with postoperative analgesia with promedol and ketorolac (a control group). The course of anesthesia and the period of early postanasthesia adaptation, the quality of postoperative analgesia and the parameters of external respiratory function, acid-base balance, and gas composition in the arterial blood were studied; the pattern of postoperative complications was also analyzed. Results. Epidural anesthesia considerably reduced the consumption of narcotic analgesics and myorelaxants at surgery, which was followed by the accelerated early postanesthesia adaptation of patients. Postoperative analgesia adequacy was much higher in the study group patients. Postoperatively, there were significant external respiratory dysfunctions of the restrictive type in both groups; however, they were much less pronounced in the study group. In the postoperative period, the control patients were observed to have significant and persistent hypoxemia, presumably associated with the development of microatelectases. There was a reduction in the incidence of respiratory and surgical complications in the study group. Conclusion. Prolonged epidural anesthesia versus anesthesia with narcotic analgesics used during high-risk abdominal surgery accelerates early postanesthesia adaptation and ensures a more adequate postoperative analgesia, resulting in a reduction in the severity of external respiratory dysfunction and impaired blood gas composition, by leading to a decrease in the incidence of postoperative complications. Key words: epidural anesthesia, surgery, external respiratory function, hypoxemia, complications.